2020
DOI: 10.1093/cid/ciaa1829
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Onchocerciasis Elimination Using a “Test-and-not-treat” Strategy in Loa loa Co-endemic Areas

Abstract: Background Mass drug administration (MDA) with ivermectin is the main strategy for onchocerciasis elimination. Ivermectin is generally safe but associated with serious adverse events in individuals with high Loa loa microfilarial densities (MFD). Therefore, ivermectin MDA is not recommended in areas where onchocerciasis is hypo-endemic and L. loa is co-endemic. To eliminate onchocerciasis in those areas, a test-and-not-treat (TaNT) strategy has been proposed. We investigated whether onchocerc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…A simplified connectivity between villages was included before in ONCHOSIM model studies, as well as in studies with the related LYMFASIM model for lymphatic filariasis; a fixed parameter function termed the external force of infection was used to explain stable low prevalence settings [ 23 , 24 ]. This parameter basically corresponds to the relatively simple case of flies being blown only from a high to a low prevalence area, as one of the options modelled here.…”
Section: Discussionmentioning
confidence: 99%
“…A simplified connectivity between villages was included before in ONCHOSIM model studies, as well as in studies with the related LYMFASIM model for lymphatic filariasis; a fixed parameter function termed the external force of infection was used to explain stable low prevalence settings [ 23 , 24 ]. This parameter basically corresponds to the relatively simple case of flies being blown only from a high to a low prevalence area, as one of the options modelled here.…”
Section: Discussionmentioning
confidence: 99%
“…Expert consultations and detailed analyses of available data spearheaded by APOC concluded that alternative treatment strategies (ATS), including those with more effective drugs than ivermectin, are needed to eliminate parasite transmission in many areas [ 22 ]. Research into different types of ATS [ 23 ] is ongoing, including discovery and development of more effective drugs [ 24 26 ], identification of effective, affordable, and sustainable complementary vector control strategies [ 27 ] and studies for implementation of new ‘test-and-not-treat’ or ‘test-and-treat’ strategies for Loa-loa co-endemic areas [ 28 32 ]. Furthermore, research for a vaccine is continuing [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, at prevalence ≥ 15%, serological tests provide a more reliable estimate than at lower prevalence, where more false positives tend to occur [ 21 ]. Another factor that should be taken in account is that mass administration of ivermectin would be challenging in Loa loa endemic areas due to the known risk of potentially fatal encephalopathy in patients with high microfilarial blood density [ 25 ].…”
Section: Discussionmentioning
confidence: 99%